Gig economy: the rise of freelancers & its impact on Human Resource (HR) - Ismail, Fadillah; Abdul Kadir, Adibah; Mohd Rosli, Nur Amalina; Mohd Noor, Norasmiha (Penerbit Uthm, 2019)
The platform labour economy has produced opportunities for flexible work and business innovation, yet it has likewise made critical monetary, social, and personal challenges for labourers. Gig work is problematic, which means usually low paid, brief, gives no well-being, preparing, or retirement advantages, and moves a greater amount of the danger of working together from the business to the contractual worker. Precarious work is related with well-being and social disparities (OECD, 2015; PEPSO, 2013), and certain defenceless gatherings have all the earmarks of being over represented in the gig economy – for example youngsters (millennial) and individuals on lower salaries (see: Balaram, Warden, & Wallace-Stephens, 2017; Block & Hennessy, 2017). This strain among need and opportunity (or push and force) is reflected in the wording used to depict gig work. For example, reporters concentrated on the advantages to firms and the perfect conceivable outcomes allude to this wonder as the "sharing," "synergistic," or "imaginative" economy (Botsman, 2013; Kuek et al., 2015; Schor, 2014), while others concentrated on the possibly negative consequences for laborers' prosperity have named it the "gig," "1099," or "chip away at interest" economy, notwithstanding describing specialists as the "precariat" (Block & Hennessy, 2017; Kalamar, 2013; Kenney & Zysman, 2016; Schor, 2016).